"Behind Those Screens" — Bringing Women Forth: Christina Rossetti and Elizabeth Siddal. Issue 1 (14th January 2020) - Cunha, Mariana Bicudo Castelo Branco
This article explores the connections between two Pre-Raphaelite women: Christina Rossetti and Elizabeth Siddal. Although they are remembered quite differently, the former as a celebrated poet, the latter as the eternal model, both women share common sufferings and artistic themes. In bringing them forth, the article aims to shed light on how Victorian society may have impacted their life and work. The accuracy of various reports of frailty and poor health regarding the artists is inspected. The article ponder on why Siddal's artistic output lingers in the shadows, while recognizing the influence of the class system and of gender roles on the lives of these women. This task is achieved through an analysis of selected works which display some of the artists' central motifs. To conclude, the article assesses the societal restrictions which pervade the works of Rossetti and Siddal, how they attempt to bend or bypass them, and in which ways these shaped their well-being and artistic recognition.